Cover Jurnal Fitopatologi Vol. 17 No. 2, Maret 2021 - Sri Hendrastuti Hidayat (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2021)
This editorial contains the front cover, editorial page and back cover of the Indonesian Journal of Phytopathology, Volume 17, No. 2, March 2021.